Development of PCR primers from internal transcribed spacer region 2 for detection of Phytophthora species infecting potatoes. - Tooley, P W (1997)
We developed PCR primers and assay methods to detect and differentiate three Phytophthora species which infect potatoes and cause late blight (Phytophthora infestans) and pink rot (P. erythroseptica and P. nicotianae) diseases. Primers based on sequence analysis of internal transcribed spacer region 2 of ribosomal DNA produced PCR products of 456 bp (P. infestans), 136 bp (P. erythroseptica), and 455 bp (P. nicotianae) and were used to detect the pathogens in potato leaf (P. infestans) and tuber (P. infestans, P. erythroseptica, and P. nicotianae) tissue with a sensitivity of 1 to 10 pg of DNA. Leaf and tuber tissue were processed for PCR by a rapid NaOH method as well as a method based on the use of commercially available ion-exchange columns of P. infestans primers and the rapid NaOH extraction method were used to detect late blight in artificially and naturally infected tubers of potato cultivar Red LaSoda. In sampling studies, P. infestans was detected by PCR from artificially infected tubers at 4 days postinoculation, before any visible symptoms were present. The PCR assay and direct tissue extraction methods provide tools which may be used to detect Phytophthora pathogens in potato seedlots and storages and thus limit the transmission and spread of new, aggressive strains of P. infestans in U.S. potato-growing regions.